Multifunctional metal organic framework and carbon nanotube-modified filter for combined ultrafine dust capture and SO2 dynamic adsorption. Issue 12 (16th November 2018) - Feng, Shasha; Li, Xingya; Zhao, Shuaifei; Hu, Yaoxin; Zhong, Zhaoxiang; Xing, Weihong; Wang, Huanting
Abstract : Ultrafine dust and acid polar gas species (SO2, NO x, H2 S, etc. ) in the atmosphere have severe effects on human health. Abstract : Ultrafine dust and acid polar gas species (SO2, NO x, H2 S, etc. ) in the atmosphere have severe effects on human health. They are the most important indices for air quality evaluation. In this work, we developed a multifunctional, metal organic framework (MOF: UiO-66-NH2 ) and carbon nanotube (CNT)-modified filter for efficient ultrafine dust removal and acid gas adsorption. A thin layer of amine-functionalized CNTs was used to construct network skeletons on a polytetrafluoroethylene (PTFE) substrate and acted as an intermediate between the porous MOF nanoparticles and the PTFE substrate. The pore size of the filter was successfully regulated from 5.1 to 2.1 μm while the modified filter still had a high gas permeability of up to 402 m 3 m −2 h −1 kPa −1 . This well-designed multifunctional filter showed an extremely high capture efficiency (99.997%) for ultrafine dust (diameter ∼0.3 μm) and SO2 adsorption capacity in dynamic filtration. Our filter with hierarchical structures is very promising for indoor air purification.